Optimizing The EFL Learning Through Individualized Education Programs for Intellectually Disability Students - Rosnaningsih, Asih; Ina Magdalena; Sumiyani; Dayu Retno Puspita; Ratih Ayu Wulandari; Haryati (UNIB Press, 2023)
This research aims to describe the English language learning process using Individual Education Program (IEP) in inclusion classes at elementary school level. This research used a qualitative approach with two students with special needs with intellectual disabilities (ID) as the subjects of this research. Three types of data collection techniques used were structured observation, structured interviews and document study. The result of this research indicated that even though the two research subjects have intellectual disability, they can still participate in learning with certain terms and conditions. Every class teacher and special assistant teacher must pay attention to students’ learning needs that supports their learning development which must be in accordance with curriculum objectives. Therefore, teachers must be able to develop the Individualized Education Program (IEP) according to the special needs of students and carry out teaching according to plans that have been made previously. Keywords: Individualized Education Program, Intellectual Disability, students with special needs